Pathological Diagnosis of Systemic Amyloidosis in a New Zealand White Rabbit - LIN Qingqing; DAI Jinlong; CHEN Zhisen; GUO Jianmin; YANG Wei (Shiyan dongwu yu bijiao yixue, 2024)
ObjectiveTo provide a reference for the diagnosis of amyloidosis in experimental animals through the pathological diagnosis of systemic amyloidosis in a case of a New Zealand white rabbit.MethodsIn a 6-month repeated ocular toxicity study, an abnormal finding was noted during the routine gross anatomical examination of one New Zealand white rabbit. Its organs were prepared as paraffin sections and stained with hematoxylin-eosin (HE) staining and Congo red staining. The histopathological features were observed under optical and polarized light microscopy.ResultsGross anatomical examination of the animal revealed an enlarged spleen and changes in the color and texture of the lung. HE staining showed that the splenic tissue structure was destroyed, the white pulp of the spleen was surrounded by dense amyloid deposition in the form of nodular rings, along with pressure atrophy of the white pulp. Amyloid deposits were also observed in the submandibular lymph nodes, mesenteric lymph nodes, ileum, sacculus rotundus, vermiform appendix, jejunum, cecum, and rectum. Congo red staining showed that the amyloid deposition in the affected organs appeared salmon-pink, and exhibited characteristic apple green birefringence under polarized light microscopy.Conclusion The histo-pathological features of the New Zealand white rabbit are consistent with the diagnostic characteristics of systemic amyloidosis.